Effects of maternal anxiety disorders on infant self-comforting behaviors: the role of maternal bonding, infant gender and age - Müller, Mitho; Tronick, Ed; Zietlow, Anna-Lena; Nonnenmacher, Nora; Verschoor, Stephan; Träuble, Birgit (Psychopathology, 2016)
Background/Aims: We investigated the links between maternal bonding, maternal anxiety disorders, and infant self-comforting behaviors. Furthermore, we looked at the moderating roles of infant gender and age. Methods: Our sample (n = 69) comprised 28 mothers with an anxiety disorder (according to DSM-IV criteria) and 41 controls, each with their 2.5- to 8-month-old infant (41 females and 28 males). Infant behaviors were recorded during the Face-to-Face Still-Face paradigm. Maternal bonding was assessed by the Postpartum Bonding Questionnaire. Results: Conditional process analyses revealed that lower maternal bonding partially mediated between maternal anxiety disorders and increased self-comforting behaviors but only in older female infants (over 5.5 months of age). However, considering maternal anxiety disorders without the influence of bonding, older female infants (over 5.5 months of age) showed decreased rates of self-comforting behaviors, while younger male infants (under 3 months of age) showed increased rates in the case of maternal anxiety disorder. Conclusions: The results suggest that older female infants (over 5.5 months of age) are more sensitive to lower maternal bonding in the context of maternal anxiety disorders. Furthermore, results suggest a different use of self-directed regulation strategies for male and female infants of mothers with anxiety disorders and low bonding, depending on infant age. The results are discussed in the light of gender-specific developmental trajectories.
Gesehen am 29.09.2020